Dal suono alla parola - Brandi, Luciana (Firenze University Press, 2004)
An up-to-date manual conceived to guide the reader through the most interesting and recent theories in the vast field of psycho-neuro-linguistics. After a review of the latest theories on the perception and production of language in adult and developmental age, the most recent studies on the relations between anatomy and cerebral functions are also discussed, opening up new perspectives on the study of language too.